Conversion of cyclic xylose into xylitol on Ru, Pt, Pd, Ni, and Rh catalysts: a density functional theory study. Issue 46 (23rd November 2021) - Akpe, Shedrack G.; Choi, Sun Hee; Ham, Hyung Chul
Abstract : Lack of theoretical investigation on xylose hydrogenation to xylitol on a catalyst's surface, limits accurate understanding of reaction processes and catalyst design. Abstract : There is currently no theoretical study on the hydrogenation of xylose to xylitol on a catalyst's surface, limiting proper understanding of the reaction mechanisms and the design of effective catalysts. In this study, DFT techniques were used for the first time to investigate the mechanisms of xylose to xylitol conversion on five notable transition metal (TM) surfaces: Ru(0001), Pt(111), Pd(111), Rh(111), and Ni(111). Two transition state (TS) paths were investigated: TS Path A and TS Path B. The TS Path B, which was further subdivided into TS Path B1 and B2, was proposed to be the minimum energy path (MEP) for the reaction process. According to our computational results, the MEP for this reaction begins with the structural rearrangement of cyclic xylose into its acyclic form prior to step-wise hydrogenation. The rate-determining step (RDS) on Ru(0001), Pt(111), Pd(111), and Ni(111) was discovered to be the ring-opening process via C–O bond scission of cyclic xylose. On Rh(111), however, the RDS was found to be the first hydrogenation stage, leading to the hydrogenation intermediate. Furthermore, based on the RDS barrier, our results revealed that the activities of the tested TM surfaces follow the trend: Ru(0001) > Rh(111) ≥ Ni(111) > Pd(111) > Pt(111). This result demonstrates the higher activity of Ru(0001) compared to other surfaces used for xylose hydrogenation. It correlates with experimental trends in relation to Ru(0001) superiority and provides the basis for understanding the theoretical design of economical and more active catalysts for xylitol production.